Approaching the religious psychiatric patient in a secular country: Does "subalternalizing" religious patients mean they do not exist?. (July 2019) - Nissen, Ricko Damberg; Gildberg, Frederik Alkier; Hvidt, Niels Christian
This article presents the findings of an empirical research project on how psychiatrists in a secular country (Denmark) approach the religious patients, and how the individual worldview of the psychiatrist influences this approach. The study is based on 22 interviews with certified psychiatrists or physicians in psychiatric residency. The article presents the theoretical and methodical grounding and introduces the analytical construct "subalternalizing, " derived from subaltern studies. "Subalternalizing" designates a process where a trait in one worldview (patient) is marginalized as a consequence of another worldview's (psychiatrist) "disinterest." The analysis located four categories: (a) religion as a negative part of the patient story, (b) religion as a positive part of the patient story, (c) religion in relation to radicalization, and (d) there are no religious patients. The discussion shows that the approach is influenced by the psychiatrist worldview. Examples of "subalternalizing" are given and how this excludes "positive religious coping" and "existential and spiritual care" from treatment.